Legal and constitutional history of India - Jois, M.Rama (Bombay: N.M. Tripathi, 1984)
Contents:vol.1.Ancient legal, judicial and constitutional system(xxiv, 723 p.).-vol.2.Modern legal, judicial and constitutional system(xx, 388 p.)
Library has 2 volume only.
Includes bibliographical references (707 p. - 711 p.) and index.